Gender differences in disordered eating and weight dissatisfaction in Swiss adults: Which factors matter? - Forrester-Knauss Christine; Zemp Stutz Elisabeth (BMC, 2012)
Abstract Background Research results from large, national population-based studies investigating gender differences in weight dissatisfaction and disordered eating across the adult life span are still limited. Gender is a significant factor in relation to weight dissatisfaction and disordered eating. However, the reasons for gender differences in these conditions are still poorly understood. The aim of this study was to examine gender differences in weight dissatisfaction and disordered eating in the general Swiss adult population and to identify gender-specific risk factors. Methods The study population consisted of 18156 Swiss adults who completed the population-based Swiss Health Survey 2007. Self-reported weight dissatisfaction, disordered eating and associated risk factors were assessed. In order to examine whether determinants of weight dissatisfaction and disordered eating (dieting to lose weight, binge eating, and irregular eating) differ in men and women, multivariate logistic regressions were applied separately for women and men. Results Although more men than women were overweight, more women than men reported weight dissatisfaction. Weight category, smoking status, education, and physical activity were significantly associated with weight dissatisfaction in men and women. In women, nationality and age were also significant factors. Gender-specific risk factors such as physical activity or weight category were identified for specific disordered eating behaviours. Conclusions The results suggest that gender specific associations between predictors and disordered eating behaviour should be considered in the development of effective prevention programs against disordered eating.